INFLUENCE PERCEIVED ORGANIZATIONAL SUPPORT, WORK CULTURE, AND EMPLOYEE PLACEMENT ON THE PERFORMANCE OF RADIO REPUBLIK INDONESIA EMPLOYEES - Devi Roro Safitri; Hafidulloh; Gogi Kurniawan; Dani Rohmati (Yayasan Nuraini Ibrahim Mandiri, 2026)
The rapid advancement of digital technology and the increasing demand for high-quality public broadcasting services require Radio Republik Indonesia (RRI) to continuously improve employee performance. This study aims to analyze the influence of perceived organizational support, work culture, and employee placement on employee performance at Radio Republik Indonesia (RRI) Regional Station Surabaya, East Java, Indonesia. The study employed a quantitative approach with an explanatory research design. The population consisted of 62 employees, all of whom were selected as respondents using a census technique. Data were collected through a structured questionnaire using a five-point Likert scale and analyzed using multiple linear regression. The results indicate that perceived organizational support has a positive and significant effect on employee performance (t = 4.763; p = 0.000). Work culture also has a positive and significant effect on employee performance (t = 2.766; p = 0.008), as does employee placement (t = 2.465; p = 0.018). Simultaneously, perceived organizational support, work culture, and employee placement significantly influence employee performance. Among the three variables, perceived organizational support emerged as the most dominant factor affecting employee performance. These findings highlight the importance of organizational support, a positive work culture, and competency-based employee placement in enhancing employee performance within public broadcasting organizations facing the challenges of digital transformation